Pelatihan Pembuatan Masker Sebagai Upaya Antisipasi Penyebaran Covid-19 di Desa Anyar Kabupaten Lombok Utara - Sucika Armiani; Siti Rabiatul Fajri; Akhmad Sukri; Baiq Yulia Pidiawati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The Covid 19 pandemic is a serious problem that must be dealt with immediately. The use of masks is an effort to minimize transmission of viruses between humans. The high demand for masks, especially medical masks, is causing scarcity in the market. Therefore, cloth masks are needed as an alternative for the community to be used daily in the midst of activities facing health crises that occur. The purpose of this community service activity is to transfer sewing skills to the Anyar Village LPM partners who are members of the